Resibufogenin inhibits the growth of human osteosarcoma MG-63 cells via mitochondrial pathway (Bangladesh Journal of Pharmacology, 2014)
Resibufogenin, a low molecular weight bufanolide steroid compound, is isolated from the secretion of Asiatic toad Bufogargarizansa Cantor. It possessed both pharmacological and toxicological effects that were experimentally shown by in vitro and in vivo studies. However, the molecular mechanism of cell apoptosis induced by resibufogenin remains elusive. Here, we investigated the apoptosis in resibufogenin-treated human osteosarcoma MG-63 cells. The results showed that resibufogenin could inhibit cell proliferation and induce apoptosis in a dose- and time-dependent manner. Additional investigations proved that a disruption of mitochondrial transmembrane potential and an up-regulation of reactive oxygen species (ROS) in resibufogenin-treated cells were occurred. Upon western blot analysis, it was found that the up-regulation of Apaf-1, cleaved PARP, cleaved caspase-3, cleaved caspase-9, and Bax/Bcl-2, varied with different concentration of resibufogenin. Overall findings suggested that resibufogenin could be used as an effective anti-tumor agent in therapy of osteosarcoma.